Family language policy in the context of return migration: A case study - Wąsikiewicz-Firlej, Emilia; Daly, Michelle (Glottodidactica, 2023)
Return migration has probably been granted the lowest attention in the field of family language policy (FLP). The current paper seeks to address this gap in the research and explores the dynamics of FLP of a Polish family in the context of their temporary migration to Germany and return migration to Poland. The authors investigate how mobility affects FLP, especially towards L1 (Polish) and L2 (German) in the context of migration and return migration. The study takes a qualitative, interview-based study design, supported by the language portrait technique. An analysis of the interview data has evidenced the parents’ strong support for the maintenance and development of L1 throughout the whole process of migration and return migration and the lack of it in the case of L2 after the return to Poland. The results have also evidenced that individuals in a family, including children, have significant autonomy and agency and can shape their independ- ent FLPs, which are aligned neither with their parents nor siblings.